? The Vicious Circle of Socio-Economic Underdevelopment, How Can Sudan breakthrough - Khairi, Gassoum Khairi Bilal (Journal of Economic, Administrative and Legal Sciences, 2018)
The purpose of this research paper is to shed light on the problems of Sudan economy reflecting on, the lack of efficient strategic planning, and well planned policies that, may help achieving its objectives. *The use of the above title” Vicious Circle of underdevelopment” is merely denoting the continuous underdevelopment in all aspects of the economy and failure of policies to achieve any positive movement toward achieving sustainable development.In this research and through analyzing the available statistical and other available data, we came out with finding that, highlight the inefficient policies applications followed in the agricultural sector which represent the spear head of the economy. The use of old technologies and lack of scientifically knowledge based methods of fertilizing, irrigation and pest control led to poor land productivity and low returns from exports. However, the policy chosen by the government to neglect the agricultural sector and rely completely on quick revenues from petrol and Gold sales proved to be disastrous to the economy. This policy option became useless with the session of Southern Sudan in 2011, carrying away75% of the petrol reserves of the country and hence, the conclusion is that no policy option is left for the government other than to go back again and try to revive the destroyed agricultural sector. In the light of this situation and based on some initiatives raised by the private sector, through introducing scientific use of modern technology in agriculture, the same land generated a very high productivity level, that raised ambitions that, this sector can be the driving engine of the economy. That happened during the harvesting season of the year2017.On the basis of this successful efforts I thought of offering a new approach in terms of policy options that may help explode the capacities of the agricultural sector through agro-industrialization and new modern marketing techniques. This was supplemented with some salient recommendations that may contribute towards more successful achievements in this sector.
Keywords: Economic Problems; Productivity; Exports; New Technologies Policies; Agro-industrialization